Perancangan dan Implementasi Sistem Informasi Manajemen dan Layanan Administrasi Kelurahan Berbasis Web Menggunakan Metode Rapid Application Development (RAD) (Studi Kasus: Kantor Kelurahan Buaran) - Muhamad Quraisy; Syafril Chairiansyah (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
An Information System is a system that uses computer technology to collect, process, store, analyze and disseminate information. The information system of administrative services and information management of the urban village is intended to increase efficiency in terms of public service as well as honorary employees in Buaran Village. Therefore, further research is needed to float this application. The purpose of making this application is to provide convenience for village officials in managing services as well as information services to provide efficiency in community services. The next steps taken in this case are system analysis, design and testing of the system. This implementation uses the PHP programming language and as a database uses MySQL. This research can be concluded that this application can be used to handle administrative service processes and personnel activities so that this information system is expected to provide some convenience for sub-district employees at the Buaran Village office.